1968
DOI: 10.2134/agronj1968.00021962006000020003x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Conditions on the Growth of Four Perennial Grasses. I. Response to Controlled Temperature1

Abstract: The growth of timothy (Phleum pratense L.), bromegrass (Bromus inermis Leyss.), orchardgrass (Dactylis glomerata L.), and Kentucky bluegrass (Poa pratensis, L.) was studied under controlled temperatures varying by 3.3 C intervals from 18.3 to 34.8 C during the day and from 1.8 to 18.3 C during the night. A day temperature between 18.3 and 21.6 C was optimum for top growth with timothy, orchardgrass, and bluegrass. With bromegrass, the optimum day temperature was between 18.3 and 24.9 C. As the day temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 3 publications
(3 reference statements)
1
33
0
Order By: Relevance
“…In temperate species, such as Buomus, Phleum, Poa and to a lesser extent Dactylis, no clear optimum day/night temperature combinations were obtained (Baker and Jung 1968), although in Phalauis and Festuca species, respective apparent optimum daylnight temperature combinations of 24119°C (Scurfield 1963) and 23117°C (Robson 1973) were obtained.…”
Section: ("C)mentioning
confidence: 92%
“…In temperate species, such as Buomus, Phleum, Poa and to a lesser extent Dactylis, no clear optimum day/night temperature combinations were obtained (Baker and Jung 1968), although in Phalauis and Festuca species, respective apparent optimum daylnight temperature combinations of 24119°C (Scurfield 1963) and 23117°C (Robson 1973) were obtained.…”
Section: ("C)mentioning
confidence: 92%
“…Above 24 C, growth subsides first and then at very high temperatures, severe injury or death can occur. In controlled environment pot experiments, Kentucky bluegrass (Poa pratensis L.) produced maxi· 79 mum dry weight of top growth at 21.6 C, and growth declined as temperature was increased to 24.9 C, Baker and Jung (1968). Plants grown at 34.8 C produced less than half the top growth of those at 21.6 C. Julander (1945) observed that Kentucky bluegrass was killed when exposed to 48 C for 16 hours.…”
mentioning
confidence: 99%
“…The relative im· portance of the two in turfgrass culture is not known. Several studies have been done on the influence of prolonged periods of moderately high temperature on turfgrass growth (Baker and Jung, 1968;Watschke et al, 1972;Pellett and Roberts, 1963). Less information is available on the effects of short exposure to high temperature.…”
mentioning
confidence: 99%
“…They also found the optimum temperature for growth to be 18.3 ºC, and stated that day temperature had a greater influence on growth than night temperature. Baker & Jung (1968a) noted a significant decline in smooth brome growth as day temperature increased from 31.0 to 35.0 ºC.…”
Section: Resultsmentioning
confidence: 95%